Optimal timing of near‐term delivery in different ethnicities: a national cohort study. (3rd July 2014) - Kazemier, BM; Ravelli, ACJ; de Groot, CJM; Mol, BWJ
Abstract : Objective: To study possible ethnic disparities in perinatal mortality and morbidity independent of the occurrence of pregnancy complications. In addition, to study the probabilities of adverse neonatal outcome for delivery, compared with 1 week of expectant management for each week of gestational age in the range of 36–42 weeks of gestation. Design: National cohort study. Setting: The Netherlands. Population: All women who were recorded as being of white European (982 318), Mediterranean (94 130), or African‐Caribbean (25 253) descent with singleton cephalic births delivered between 36 +0 and 42 +6 weeks of gestation. Women with hypertension, pre‐eclampsia, or diabetes, or with fetuses that were small for gestational age (below the tenth percentile) or with congenital abnormalities, were excluded. Data were obtained from the Netherlands Perinatal Registry (1999–2007). Methods: Numbers of antepartum and intrapartum/neonatal death, and neonatal morbidity, were expressed using the fetus/neonate‐at‐risk approach. For each week of gestation, we compared the probability of adverse neonatal outcome (intrapartum/neonatal death in that week) for delivery with the probability of adverse neonatal outcome for expectant management (antepartum death in that week plus intrapartum/neonatal death and morbidity in the subsequent week). Results: Women of Mediterranean and African‐Caribbean descent who were near term were at increased risk of antepartum and intrapartum/neonatal death, and neonatal morbidity, compared with white European women. Expectant management from 40 weeks of gestation onwards was associated with an increased probability of adverse neonatal outcome in white European women and in women of Mediterranean descent, compared with delivery (risk ratio, RR 1.45, 95% confidence interval, 95% CI 1.25–1.68, versus RR 1.69, 95% CI 1.11–2.60, and with number needed to deliver to prevent one adverse neonatal outcome being 563 and 364, respectively). This was not observed for women of African‐Caribbean descent. Conclusions: Ethnic disparities in perinatal outcomes were observed, with higher risks for women of Mediterranean descent. Expectant management in white European and Mediterranean women after 39 weeks of gestation is associated with an increased risk of adverse neonatal outcome.